The quality of traditional streets in Indonesia - Sholihah, Arif Budi (2016)
In the past few decades, the cities of Indonesia have experienced rapid development, with the transformation sometimes leading to improvements but often having a devastating impact on the urban environment. A worrying trend has been the reduction of the role of urban traditional streets in Indonesia as mixed-use and vibrant public places to become purely channels of movement, especially for car-based traffic. For this reason, this research focuses on assessing the quality of traditional streets in Indonesia and is being conducted before they disappear as a result of rapid development in urban areas. The primary aim of the research is to demonstrate the role of traditional streets in shaping the urban environment and urban public life. In this context, the research focuses on critically examining the distinctive characteristics of such streets through street quality indicators that have been developed in urban design discourses. A qualitative inquiry is chosen as the main research method with multiple case studies and a research strategy based on research questions, research knowledge, and expertise. The techniques to gain data were field observations (walk-by observations, pedestrian counts, and behavioural mapping) and in-depth interviews. The analysis procedure was a rationale-inductive method and relied on the data from the field work as the emerging information (data-led analysis). The research concludes that there are five major characteristics of traditional streets that play important roles to support urban public life; these are: the physical and visual quality of the street; traditional street as mixed-use urban space; as multi-cultural urban space; as a cultural path and public space of the city; and traditional street activities as intangible culture. The results of the study confirm the earlier findings that suggest that Asian street are vibrant places with mixed-use pavements that contribute significantly to the vibrancy of the city. This study adds to the knowledge of the potential of the traditional street in Indonesia as one of the primary urban spaces, as public space, as creative space, as cultural space, and as urban heritage that should be safeguarded and conserved for its outstanding value not only for its architectural diversity, but also for its intangible cultures. The research also recognises the important role of traditional streets in Indonesia to the contemporary city. The recognition of the integral entity of these streets including their economic, social, and the cultural life of the surrounding context have led to a better understanding in terms of research and can be part of the foundation to formulate better policy and design intervention for the future of Indonesian cities.